Digital Rebranding and Quotidian Self-Reinvention: Wellness Influencer-Healers’ Negotiations of Authenticity and Tellability Crises on Instagram - Ali, Maxine (Narrative Works, 2025)
This paper examines practices of digital rebranding, characterised as the strategic overhaul and staged revitalization of one’s digital persona, within wellness influencer cultures on Instagram. Processes of rebranding, which are communicatively afforded by and performatively augmented through platform tools, features and semiotic resources, introduce a narrative disjuncture that requires delicate rhetorical management of self-historicity in relation to neoteric self-presentation practices in order to preserve impressions of authenticity. Drawing on data collected during a longitudinal blended digital ethnographic study, including screen-based participant observations, social media content extraction and oral interviews, I explore the ways in which female wellness influencer-healers discursively (re)negotiate their self-positioning in connection to their current and past digital brands and, relationally, their (imagined) audiences. I suggest that rebranding practices are narratively structured by and, in turn, enact authenticity through discourses of ‘personal growth’ and ‘pedagogical self reflection,’ thereby constructing self-presentational shifts as emergent and organic evolutions in one’s online presence. The paper further argues that digital rebranding manifests from compounded crises of authenticity and tellability, compelling users to continuously recalibrate their online personas in alignment with evolving platform norms and audience expectations. The analysis therefore foregrounds the paradoxical struggle of maintaining a stable personal brand whilst adapting to the dynamic nature of social media.